RISE OF ISLAMPHOBIA IN EUROPE: IMPACTS ON MUSLIMS DIASPORA - Naila Saleem; Faisal Abdullah Khan; Abdul Ghaffar (International Journal of Contemporary Issues in Social Sciences, 2024)
In the contemporary globalized world where people and societies are deeply connected in socio-political and economic interactions, the use of populism and its divisive manifestation-identity politics has a potential to inflict bruises and damages in the relationship of two great civilizations, hence undermining European social order and their political relationship with the Muslim World. Muslims in Europe are suffering from hate and discrimination at different levels and in different ways. Incidents involves the burning of Holy Book Quran, attacks on Mosques, killing of Muslims, hate speeches against Muslims etc. The term Islamophobia is frequently used by the politicians and left wing leaders to gain their desired goals. Religion Islam is correlated with terrorism and terrorists with Muslims which is totally wrong. The main reason is the misunderstanding that lies in most of the Europeans and the wrong projection of Religion Islam by the western media. There is a need to address the issue and to project the true meanings of Islam to the entire world. Where post 9/11, economic crisis of 2008, populist wave, leftist leaders are causing Islamophobia, the Muslims Migrants influx has caused the rise of Islamophobia in Europe.